A NOTE ON PORTFOLIO CHOICE AND BEHAVIORAL FINANCE: SOME FOOD FOR THOUGHT - PFIFFELMANN, MARIE; ROGER, PATRICK (Bankers, Markets & Investors, 2021)
In this note, we invite the reader to think about behavioral portfolio choice as a deviation from the standard Markowitz problem. The deviation has three origins; 1) the objective function to be maximized, 2) the probability measure under which prices and returns are characterized, and finally 3) the domain over which the optimization problem is solved. We then provide an illustration, from the Behavioral Portfolio Theory (BPT) of Shefrin and Statman (2000) to a set of relevant portfolio performance measures in a behavioral framework.